Trends in the disease burden of HBV and HCV infection in China from 1990-2019. (September 2022) - Yue, Tingting; Zhang, Quanquan; Cai, Ting; Xu, Ming; Zhu, Haizhen; Pourkarim, Mahmoud Reza; De Clercq, Erik; Li, Guangdi
Abstract: Objectives: This study aimed to reveal the 30-year dynamics of hepatitis B virus (HBV) and hepatitis C virus (HCV) disease burden in China from 1990-2019. Methods: HBV/HCV data were retrieved from the Global Burden of Disease database. Joinpoint regression was used to examine temporal trends. Age-period-cohort models were applied to evaluate effects of patient age, period, and cohort on HBV/HCV-associated mortality and incidences. Results: A dramatic decrease in the disease burden of HBV was found from 1990-2019, but the disease burden of HCV has remained stable since 2000. Patient age, period, and cohort exerted a significant effect on the diseases burden of HBV and HCV infection. Compared with women, men had a higher risk of HBV/HCV infections as well as HBV/HCV-associated mortality and liver cancer. Overweight, alcohol, tobacco, and drug use were important risk factors associated with HBV/HCV-associated liver cancer. The incidences of HBV- and HCV-associated liver cancer from 2019-2044 are expected to decrease by 39.4% and 33.3%, respectively. Conclusion: The disease burden of HBV/HCV infection has decreased in China over the past 30 years, but HBV incidences remain high, especially in men. Effective management of HBV and HCV infections is still needed for high-risk populations.